Tulipmania - Garber, Peter M. (Journal of Political Economy, 1989)
Though it is always mentioned first among the list of obvious manias, no serious effort has ever been expended to investigate the market fundamentals that might have driven the tulip speculation. This paper compiles time series on individual tulip prices and examines market fundamentals potentially driving prices. Most of the "tulipmania" was not obvious madness. High but rapidly depreciating prices for rare bulbs is a typical pattern in the flower bulb industry. Only the last month of the speculation, during which common bulb prices increased rapidly and crashed, remains as a potential bubble.